1997
DOI: 10.1017/s0022112097005521
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal forcing of a turbulent separation bubble

Abstract: A turbulent separation bubble is forced by single- and double-frequency sinusoidal disturbances, with the emphasis placed on the reattachment length as a function of the forcing amplitude and frequency. The separation bubble is that formed along the side of a blunt circular cylinder with a square leading edge. In single-frequency forcing, the reattachment length attains a minimum at a particular forcing frequency, F, which scales with the frequency of shedding of vortices from the reat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 0 publications
0
25
1
2
Order By: Relevance
“…These and other related features have important consequences in flow control, and therefore a thorough understanding of the airfoil flow at high angles of attack is an essential step toward developing effective control strategies for this technologically important flow. The complexity of this flow, however, makes both experimental and numerical investigations extremely challenging (see, e.g., [3,16,52,68,86,87,93]). …”
Section: Flow Past An Airfoilmentioning
confidence: 99%
“…These and other related features have important consequences in flow control, and therefore a thorough understanding of the airfoil flow at high angles of attack is an essential step toward developing effective control strategies for this technologically important flow. The complexity of this flow, however, makes both experimental and numerical investigations extremely challenging (see, e.g., [3,16,52,68,86,87,93]). …”
Section: Flow Past An Airfoilmentioning
confidence: 99%
“…The primary mechanism is likely to be the shedding-type instability (Nishioka et al, 1990;Sigurdson 1995) whose frequency scales with the height of the separation zone and the velocity at the separation edge ; Q . The mechanism is also interpreted as the impinging-type instability (Nakamura & Nakashima 1986;Kiya et al, 1997).…”
Section: Momentum Defect In the Near Wakementioning
confidence: 99%
“…The mechanisms of the two-dimensional periodic excitation control have been discussed for a long time. A periodic excitation is considered to promote hydrodynamic two-dimensional instability and laminar-turbulent transition downstream (Hasan, 1992;Sigurdson, 1995;Kiya et al, 1997;Talan and Hourmouziadis, 2002), although how the turbulence energy in the wake shortens the separation region length is not sufficiently well-understood. Numerous studies and comments have been reported, especially on the separation control flow around an airfoil by the periodic forcing of control devices at the leading edge (Post et al, 2003;Post and Corke, 2004;Visbal et al, 2006;Corke et al, 2011;Nonomura et al, 2013;Aono et al, 2013a;Asada et al, 2014;Sato et al, in press).…”
Section: Introductionmentioning
confidence: 99%